Penilaian Pemanfaatan Teknologi E-Business pada Industri UMKM - Noerlina Noerlina; Siti Elda Hiererra (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Contribution of MSMEs (micro, small and medium enterprises) in the economy is significant enough. It indicates the importance of support for MSMEs to maintain and double the capacity their businesses. In conducting its business, 76% of respondents already use the Internet (e-business) but still not optimally because the average does not have a website as a forum for the promotion and selling activity. Total mean score of 4.2 in adoption of innovations indicates that it has been realized, done, evaluated and adopted as a whole. Therefore, it is necessary to perform an assessment on what extent of e-business application that has been done by reviewing the readiness of MSME industries and the aspects of the utilization of information and communication technology (ICT) by MSMEs particularly of those located in Jabodetabek. The purpose of this assessment is to get an overview, status and position of the support of implementation of e-business owned and how the adoption process of e-business application can run in Jabodetabek. With the assessment of e-business technology use, we expect the planning, implementation and control of programs as well as the implementation of e-business can be conducted more directedly and controlled.